Restoration of Natural Forests After Severe Wind Disturbance in a Cold, Snowy Region With a Deer Population: Implications From 15 Years of Field Experiments - Morimoto, Junko; Sugiura, Mio; Morimoto, Miho; Nakamura, Futoshi (Frontiers in Forests and Global Change, 2021)
Questions have been raised about the application of conventional post-windthrow forest practices such as salvage logging, site preparation, and afforestation in response to the increase in wind disturbance caused by climate change. In particular, it is necessary to identify effective forest management practices that consider the pressure from deer browsing in forests in cold, snowy regions because the population of ungulates is expected to increase. The impacts of legacy destruction, i.e., the destruction of advance regeneration, microsites, and soil structure, caused by conventional post-windthrow practices have rarely been assessed separately from the impacts of subsequent deer browsing on forest regeneration or evaluated based on sufficiently long monitoring periods to assess vegetation succession. This lack of studies is one reason that alternative forest management practices to salvaging and planting have not been proposed. We conducted a field experiment at a large-scale windthrow site with a deer population to (1) assess the impact of legacy destruction and deer browsing on vegetation biomass and species composition after 15 years and (2) identify the effects of legacy retention. The study design allowed us to distinguish between and measure the impact of legacy destruction and that of subsequent deer browsing during a 15-year period. The results revealed the following: (1) Salvage logging and site preparation suppressed the development of biomass of shrub and tree layers in forested areas where harvest residues were piled up and shifted the plant communities in these areas to herbaceous plant communities. (2) Subsequent deer browsing suppressed the development of the biomass of shrub and tree layers throughout the forested site and shifted herbaceous communities to ruderal communities dominated by alien species; and 3. Compared with salvaging and planting, legacy retention enabled the windthrow sites to more quickly develop into a stand with characteristics similar to that of a mature, natural forest. Forest management practices that consider the presence of deer are necessary. We propose a policy shift from planting trees after salvaging to leaving downed trees to regenerate natural forests, unless there is concern about insect damage to the remaining forestry land in the vicinity.